2016
DOI: 10.1007/s00401-016-1659-5
|View full text |Cite
|
Sign up to set email alerts
|

A driver role for GABA metabolism in controlling stem and proliferative cell state through GHB production in glioma

Abstract: Cell populations with differing proliferative, stem-like and tumorigenic states co-exist in most tumors and especially malignant gliomas. Whether metabolic variations can drive this heterogeneity by controlling dynamic changes in cell states is unknown. Metabolite profiling of human adult glioblastoma stem-like cells upon loss of their tumorigenicity revealed a switch in the catabolism of the GABA neurotransmitter toward enhanced production and secretion of its by-product GHB (4-hydroxybutyrate). This switch w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 62 publications
(75 reference statements)
4
52
0
Order By: Relevance
“…Flavahan and colleagues demonstrated that up-regulation of the high-affinity glucose transporter GLUT3 promotes acquisition by GBM cells of tumorigenic properties [23]. Conversely, we found that decreased activity of the mitochondrial enzyme SSADH triggers GBM cell conversion into a less aggressive functioning state, by coupling enhanced levels of the GABA byproduct GHB to altered epigenetic regulations [18]. These metabolic variations have been found to take place within the patient tumors, and to be coherently linked with relevant phenotypic markers [18], or patients' clinical course [12,23].…”
Section: Introductionmentioning
confidence: 48%
See 3 more Smart Citations
“…Flavahan and colleagues demonstrated that up-regulation of the high-affinity glucose transporter GLUT3 promotes acquisition by GBM cells of tumorigenic properties [23]. Conversely, we found that decreased activity of the mitochondrial enzyme SSADH triggers GBM cell conversion into a less aggressive functioning state, by coupling enhanced levels of the GABA byproduct GHB to altered epigenetic regulations [18]. These metabolic variations have been found to take place within the patient tumors, and to be coherently linked with relevant phenotypic markers [18], or patients' clinical course [12,23].…”
Section: Introductionmentioning
confidence: 48%
“…Conversely, we found that decreased activity of the mitochondrial enzyme SSADH triggers GBM cell conversion into a less aggressive functioning state, by coupling enhanced levels of the GABA byproduct GHB to altered epigenetic regulations [18]. These metabolic variations have been found to take place within the patient tumors, and to be coherently linked with relevant phenotypic markers [18], or patients' clinical course [12,23]. Metabolism is also emerging as a player in GBM therapeutic resistance, as exemplified by escape from the anti-angiogenic Bevacizumab treatment.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…For example, in the hallmark ‘Evading Immune Detection’, we found that GO term ‘regulation of defense response to virus’ was only affected by mutually exclusive modules in HNSC, which is consistent with the prevalence and the roles of human papillomavirus in directly inhibiting innate immune system for this cancer type (Bodily and Laimins, ; Maxwell et al ., ). Similarly, GO term ‘neurotransmitter secretion’ in the hallmark ‘Self Sufficiency in Growth Signals’ was unique to GBM and LGG, in which neurotransmitters such as dopamine and GABA , have proved to govern cell proliferation (Dolma et al ., ; El‐Habr et al ., ).…”
Section: Discussionmentioning
confidence: 97%